Autoantibodies to glutamic acid decarboxylase in patients with epilepsy are associated with low cortical GABA levels. - Stagg, C; Lang, B; Best, J; McKnight, K; Cavey, A; Johansen-Berg, H; Vincent, A; Palace, J (2010)
Antibodies to glutamic acid decarboxylase (GAD), the major pathway for the synthesis of c-aminobutyric acid(GABA) in humans, are found at elevated levels in a subgroup of patients with chronic epilepsy. To test whether the antibodies were associated with changes in cortical GABA levels we used magnetic resonance spectroscopy. Four patients with epilepsy and high serum GAD antibody levels (107-6,200 units/ml) and 10 healthy controls were recruited. A 3T GABA-optimized spectrum was obtained from a reproducible voxel in the cortex. Compared to the control group, the patient group had significantly lower GABA concentrations within the cortex. Demonstration of an association between high serum GAD antibodies and low cortical GABA levels in patients with epilepsy suggests that GAD antibodies are, at least, a marker of a specific disease process and support a role for immune-mediated GABAergic dysfunction.